Benefits and Costs of Bank Capital - Dagher, Jihad (Staff Discussion Notes; Staff Discussion Notes ;, 2016)
The appropriate level of bank capital and, more generally, a bank's capacity to absorb losses, has been at the core of the post-crisis policy debate. This paper contributes to the debate by focusing on how much capital would have been needed to avoid imposing losses on bank creditors or resorting to public recapitalizations of banks in past banking crises. The paper also looks at the welfare costs of tighter capital regulation by reviewing the evidence on its potential impact on bank credit and lending rates. Its findings broadly support the range of loss absorbency suggested by the Financial Stability Board (FSB) and the Basel Committee for systemically important banks.